The art of Howl's moving castle : [a film by Hayao Miyazaki] - Miyazaki, Hayao, 1941-; Jones, Diana Wynne (San Francisco, Calif. : VIZ, 2005)
This book is a collection of concept sketches, concept art, backgrounds, character designs (including painted versions), and still images for Hayao Miyazaki's animated film, Howl's Moving Castle, based on the book by Diana Wynne Jones. All concept sketches are by Miyazaki. Concept art and backgrounds are by the art staff supervised by art director. The background art and still imageds for this book were created from digital data. Scene images without captions are sitll images.
-- part 1. Hayao Miyazaki's concept sketch collection -- part 2. Concept art, background art, character designs and concept sketches -- part 3. Final screenplay -- Credits.
"First published in Japan by Studio Ghibli Inc."--Colophon.
Based on the Howl's Moving Castle by Diana Wynne Jones.
Keywords: Creation (Literary, artistic, etc.) in motion pictures; Animation (Cinematography); Motion pictures -- Art direction; Motion pictures -- Setting and scenery